Pulse current co-deposition of Ni-WS2 nano-composite film for solid lubrication. Issue 4 (12th March 2017) - Roy, D.; Das, A. K.; Saini, R.; Singh, P. K.; Kumar, P.; Hussain, M.; Mandal, A.; Dixit, A. R.
ABSTRACT: This study was undertaken to observe the effect of nano-composite coating on steel surface for enhancing its tribological properties. In the investigation, EN31 steel surfaces were coated with nano-composite (Ni-WS2 ) by pulse current co-deposition process in order to improve the tribological properties of the surface. The coatings were prepared according to different parameter settings. The effect of variations on coating thickness, microstructure, surface morphology, microhardness and tribological properties was observed. The maximum coating thickness of 117 µm with 8% by weight of WS2 particle concentration could be attained with the following parameter settings: applied voltage: 5 V; pulse frequency: 20 Hz; WS2 concentration: 20 g/l; duty factor: 0.6 and bath temperature: 50°C. The average friction coefficient of the deposited surface was 0.11, which is significantly less than that of the EN31 steel surface (average coefficient of friction > 0.5).